Teaching Narrative Text By Using Directed Reading Thinking Activity (DRTA) To The Seventh Graders Of SMP Negeri 38 Palembang - Aelista Dwi Wahyuni; Badriyah Ulfah; Jaya Nur Iman (CV. Ulil Albab Corp, 2022)
DRTA strategy is effective in teaching and learning reading purposed to improve students’ reading comprehension. Students read the material short stories and make predictions then they read segments of the text and confirm or revise previous predictions; Finally, the steps continue until they finish reading the entire text. This study aimed to determine the effect of the method Directed Reading Thinking Activity (DRTA) in improving students'reading abilities. This research was conducted to describe the techniques of teaching reading comprehension used, and to find out how the techniques applied by the teacher in teaching reading understanding in seventh grade students of SMP Negeri 38 Palembang In this study, narrative quantitative research was used to obtain information related to research problem. Researcher used a study Experimental with a research Control Group Design. The population is a grade VII 3 and VII 4 student at SMP Negeri 38 Palembang .The sample in this study were VII 3 students as experimental class and VII 4 as control class. The data obtained from the objective test result of multiple choice as much as 50 questions then analyzed with, validity test, test reliability, questions,difficulty level test questions, normality test, homogeneity test and hypothesis. The result of data processing through statistical calculation by using pre-test and post-test to show the results in the experimental class and control class and the results showed that the experimental class has a higher value than control class so that there was a significant difference between the experimental class control class in the seventh gradestudents of SMP Negeri 38 Palembang . Thus, the methods of Directed Reading Thinking Activity (DRTA) can be used both teachers and students to improve students' reading ability.